Analisis Unsur-Unsur Intrinsik Dan Ekstrinsik Pada Puisi “The Guest House” Karya Jalaluddin Rumi - Ekayani, Ridha; Nur Sakinah, R. Myrna (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
One of Jalaluddin Rumi’s poems which is titled “The Guest House” is a poem that shows the richness of figurative language used by the poet from Sufi. This poem was made during the early Islamic world literature era, precisely in the 13th century. This study focused on analysis on Rumi’s brief profile, intrinsic elements such as theme and figurative languages, also extrinsic elements including historical and socio-cultural influences during the creation of the poem where in the context of this poem is the influence of the early Islamic world literature era. This research will examine how figurative languages used by Rumi like metaphors and personifications contribute to the poem’s emotional impact, and how the poem effectively engages the readers to adopt an attitude of acceptance toward life experiences and emotions. Through literature structuralism theory, this research aims to uncover Rumi's brilliance in crafting words to send deep spiritual messages and to provoke self-reflections to the readers.